The spectrum of alpha-resolvable lambda-fold (Ksub4 - e)-designs - Gionfriddo, Mario (Ars mathematica contemporanea, 2016)
A ?$λ$?-fold ?$G$?-design is said to be ?$α$?-resolvable if its blocks can be partitioned into classes such that every class contains each vertex exactly ?$α$? times. In this paper we study the ?$α$?-resolvability for ?$λ$?-fold ?$(K_4-e)$?-designs and prove that the necessary conditions for their existence are also sufficient, without any exception.
Keywords: kombinatorika